Self-assembled spectrum selective plasmonic absorbers with tunable bandwidth for solar energy conversion. (February 2017) - Zhou, Lin; Zhuang, Shendong; He, Chengyu; Tan, Yingling; Wang, Zhenlin; Zhu, Jia
ABSTRACT: Plasmonic nanostructures enable manipulation of light ranging from ultraviolet, visible to infrared regime based on steering on a variety of optical resonances. For various applications such as biomedical sensing, photodetectors and solar energy conversion, it is desirable to fabricate plasmonic absorbers with finely tuned bandwidth. In this work, for the first time, we report that spectrum-selective plasmonic absorbers with flexibly tuned bandwidth can be fabricated by a convenient self-assembly process. The plasmonic absorbers demonstrate an extraordinary absorption (above 90%) with absorption cutoff wavelengths flexibly tuned from visible ( 550 nm) to infrared ( 2500 nm). The pronounced absorption can be ascribed to plasmon hybridization of the close-packed gold nanoparticles, while optical cutoff effect of the gold-particle-assembly built nanotube leads to the tunable absorption edge. These tunable plasmonic absorbers also demonstrate excellent high temperature stability (up to 1073 K) with a thin alumina protection coating and applications for solar steam generation. Therefore, the plasmonic absorbers with tunable absorption bandwidth and thermal stability can serve as promising candidates for various solar energy conversion applications, such as solar steam generation, photocatalysis, etc . Graphical abstract: Highlights: Spectrum selective plasmonic absorbers from 550 to 2500 nm are demonstrated. The absorbers show highly efficient absorption capacity of 90%. The absorbers show high temperature stability (up to 1073 K). The origin of pronounced absorption and tunable bandwidth has been studied.